RETRACTED: Purification, Characterization, and Hydrolysate Analysis of Dextranase From Arthrobacter oxydans G6-4B - Liu, Nannan; Li, Peiting; Dong, Xiujin; Lan, Yusi; Xu, Linxiang; Wei, Zhen; Wang, Shujun (Frontiers in Bioengineering and Biotechnology, 2022)
Dextran has aroused increasingly more attention as the primary pollutant in sucrose production and storage. Although enzymatic hydrolysis is more efficient and environmentally friendly than physical methods, the utilization of dextranase in the sugar industry is restricted by the mismatch of reaction conditions and heterogeneity of hydrolysis products. In this research, a dextranase from Arthrobacter oxydans G6-4B was purified and characterized. Through anion exchange chromatography, dextranase was successfully purified up to 32.25 folds with a specific activity of 288.62 U/mg protein and the Mw of 71.12 kDa. 55 ℃ and pH 7.5 were the optimum reaction conditions, and it remained relatively stable in the range of pH 7.0-9.0 and below 60 ℃, while significantly inhibited by metal ions, such as Ni+, Cu2+, Zn2+, Fe3+, and Co2+. Noteworthily, a distinction of previous studies was that the hydrolysates of dextran were basically isomalto-triose (more than 73%) without glucose and the type of hydrolysates tened to relatively stable in 30 min, dextranase activity showed a great influence on hydrolysate. In conclusion, given the superior thermal stability and simplicity of hydrolysates, the dextranase in this study presented great potential in the sugar industry to remove dextran and obtain isomalto-triose.